The Implementation of High Order Thinking Skills (HOTS) Assessment to Evaluate the Students’ Reading Comprehension Achievement - Leila Nurul Amali; Dwi Anggani Linggar Bharati; Fahrur Rozi (Universitas Negeri Semarang, 2022)
HOTS promote the idea of assessing students’ critical thinking, creativity, and problem-solving. However, many teachers claimed to have difficulties in designing questions and implementing them in teaching and learning process. The present study aimed to explain how teachers perceive, implement, and assess HOTS assessment in teaching reading comprehension. It employed an exploratory sequential design. Using the purposive sampling technique, two English teachers from SMA N 1 Pati were involved. The data were gathered through semi-structured interviews, document analysis, classroom observations, and tests. This study reveals that the teachers had a good perception of HOTS assessment in terms of concept and implementation. They implemented HOTS assessment using appropriate strategies and methods in teaching reading comprehension. In addition, the teachers designed the proper assessment using HOTS assessment in assessing reading comprehension. The students’ achievement also had achieved the required score in reading comprehension. All the results aligned with teachers’ perceptions, implementations, assessments, and students’ achievement. Although the teachers had exemplary performance, they still met difficulties due to students’ needs and motivation. Therefore, it was expected for further research to conduct more detailed research in a long time to collect more valid and complete information about HOTS assessment.